Origin of enhanced VCD in amyloid fibril spectra: Effect of deuteriation and pH - Pazderková, Markéta; Pazderka, Tomáš; Shanmugasundaram, Maruda; Dukor, Rina K; Lednev, Igor K; Nafie, Laurence A (Chirality, 2017)
Supramolecular chirality of amyloid fibrils, protein aggregates related to many neurodegenerative diseases, is a remarkable property associated with fibril structure and polymorphism. Since its discovery almost 10 years ago there is still little understanding of this phenomenon, including the cause of the highly enhanced vibrational circular dichroism (VCD) intensity arising from fibril supramolecular chirality. In this study, VCD spectra, enhanced by filament supramolecular chirality, are presented for lysozyme and insulin fibrils above and below pH 2 and after deuterium exchange, above and below pD 2. Supramolecular chirality (observed by VCD) and fibril morphology (documented by atomic force microscopy) are not affected by protein deuteriation. In D2 O the fibril VCD sign pattern changes to fewer bands, with implications for the amide I/II origin of enhanced VCD intensity. Separation of amide I and II signals will facilitate calculations of enhanced VCD spectra of amyloid fibrils and enable a better understanding of the origin of the VCD sign pattern.
Keywords: Insulin; proteinové agregáty; inzulin; Protein Aggregates; supramolecular chirality; deuterium exchange; vibrational circular dichroism; Hydrogen-Ion Concentration; VCD intensity enhancement origin; Circular Dichroism; koncentrace vodíkových iontů; Deuterium; Muramidase; Animals; lidé; Humans; zvířata; cirkulární dichroismus; amyloid; protein fibrils; deuterium; Amyloid; muramidasa